2013
DOI: 10.2134/agronj2013.0137
|View full text |Cite
|
Sign up to set email alerts
|

Fall‐ and Spring‐Applied Poultry Litter Effectiveness as Corn Fertilizer in the Mid‐Southern United States

Abstract: The effectiveness of fall-or winter-applied poultry litter, relative to spring-applied litter, as row crop fertilizer in the southern and southeastern United States has not been well researched. A 3-yr field study was conducted in northern Mississippi to determine the effectiveness of litter as corn (Zea mays L.) fertilizer and quantify loss of its potency when applied in the fall. The grain yield and biomass of corn that received fall-applied poultry litter (9 or 18 Mg ha -1 ) or 202 kg ha -1 NH 4 NO 3 -N was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
3
20
2
Order By: Relevance
“…The treatments resulted in a range of fertilization levels that led to grain yield as low as ≈3 Mg ha –1 to as high as ≈10 Mg ha –1 (Tewolde et al, 2013). This range likely was due to the range of plant‐available N levels created by the rate and timing of application of the fertilizers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The treatments resulted in a range of fertilization levels that led to grain yield as low as ≈3 Mg ha –1 to as high as ≈10 Mg ha –1 (Tewolde et al, 2013). This range likely was due to the range of plant‐available N levels created by the rate and timing of application of the fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…The plots received a total rainfall of 153 mm in 2006 and 229 mm in 2007 during the growing season in May, June, and July. Monthly total rainfall and average air and soil temperature information for the study site is given by Tewolde et al (2013). The plots were kept weed free using locally established weed control practices during each growing season.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained by Sistani et al (2010) indicated that no-till corn cultivated with 13.5 Mg ha -1 year -1 of PL for four consecutive years resulted in corn grain yields similar (p > 0.05) to corn cultivated with mineral fertilization without causing residual levels of P, Cu, and Zn that could be harmful to surface waters or subsequent crops. Tewolde, Sistani, & Adeli (2013) observed that only 31% of N from an application of 18.0 Mg ha -1 of PL in the spring was released in the first year, and when compared with the fall application resulted in average increases (p < 0.05) of 14% for ear leaf N concentrations and of 24% for corn grain yields during three years.…”
Section: Introductionmentioning
confidence: 94%